2023
DOI: 10.3390/su15043313
|View full text |Cite
|
Sign up to set email alerts
|

Suitability Assessment of Small Dams’ Location as Nature-Based Solutions to Reduce Flood Risk in Mataniko Catchment, Honiara, Solomon Islands

Abstract: As global temperatures rise, flooding and storm surges caused by extreme weather threaten people’s safety and nations’ development. Nature-based Solutions (NBS) are practical actions to support resilience to reduce flood risk and are applied in many countries. As the NBS approach mentions, small check dams made of gabion and wood can retain runoff and temporarily create detention basins to reduce the magnitude of floods and provide additional water resources. However, previous dam suitability research emphasiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Another approach to NbS for dam construction is using natural materials for dam building, such as rocks, soil, and vegetation [ 103 ]. This approach can help reduce dam construction's environmental footprint and improve the dam's resilience to natural hazards, such as floods and landslides [ 104 ].…”
Section: Interpretation Of Results and Discussionmentioning
confidence: 99%
“…Another approach to NbS for dam construction is using natural materials for dam building, such as rocks, soil, and vegetation [ 103 ]. This approach can help reduce dam construction's environmental footprint and improve the dam's resilience to natural hazards, such as floods and landslides [ 104 ].…”
Section: Interpretation Of Results and Discussionmentioning
confidence: 99%
“…Recent study results reveal that small dams (storage structures) constructed by gabions and wood were considered NBS (nature-based solutions) to manage flood risk and overland flow, even in mountainous regions. Rainwater-harvesting structures control flood peaks, store runoff water, and act as a climate-change-mitigating strategy and have minimum maintenance with an ecological concept [17]. In another study in Southern Burkina Faso, supplementary irrigation found to be cost-effective and enhance income, especially during drought-prone years.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The transversal themes are flood management, green infrastructure, ecosystem services, environmental justice, and urban ecology. These themes can be found in research developed by Mabrouk et al (2023) with simulations to assess of NbS effectiveness on flood management for cities in the MENA region; Liu et al(2023) with the assessment on appropriate location of small dams as NbS option to control floods; and Raymond et al (2023) with proposed approaches in order to enable senses of place, stakeholder engagement and just city transitions towards cities that integrate NbS in its urban spaces.…”
Section: Thematic Mapmentioning
confidence: 99%